Composites of malonic acid diamides and phospholipids – Structural parameters for optimal transfection efficiency in A549 cells. Issue 9 (5th June 2014) - Janich, Christopher; Wölk, Christian; Taßler, Stephanie; Drescher, Simon; Meister, Annette; Brezesinski, Gerald; Dobner, Bodo; Langner, Andreas
<x xml:space="preserve">Abstract</x> The aggregation behavior of various zwitterionic helper phospholipids, such as DOPE, DOPC, and DPPC, in combination with two new cationic lipids, namely TH4 and OH4 (second generation of malonic acid diamides) in different molar ratios was studied with regard to their physical–chemical properties. Additionally, lipoplexes prepared from these lipid mixtures were characterized with respect to the transfection efficacy using an EGFP‐assay. The lipid mixtures with the fluid cationic lipid OH4 and DOPE have shown comparable transfection efficiency with Lipofectamine 2000®. Furthermore, this report demonstrates the huge influence of the helper lipid on the transfection efficiency. Thereby, alkyl chain fluidity, lipid miscibility and charge density have an important influence on an efficient gene transfer. Practical applications: Although lipofection is a topic of gene therapy since 1989, finding an effective lipid system with new cationic lipids is still a process of trial and error. There is much unknown about the process of lipoplex formation as well as the release of the genetic cargo. Aim of the presented work is to find physical–chemical parameters which are connected with an effective gene transfer. <inline-graphic xlink:href="ark:/27927/pgh18r8vtf1" content-type="ejlt201300405-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> This report demonstrates the influence of the cationic and helper lipid on the transfection efficiency. Thereby, alkyl chain fluidity, lipid miscibility and charge density have an important influence on an efficient gene transfer.